Responses are durable for up to 5 years after completion of peginterferon alfa‐2a treatment in hepatitis B e antigen‐positive patients. Issue 9 (9th March 2018) - Chuang, W.‐L.; Jia, J.; Chan, H. L. Y.; Han, K.‐H.; Tanwandee, T.; Tan, D.; Chen, X.; Gane, E.; Piratvisuth, T.; Chen, L.; Xie, Q.; Sung, J. J.‐Y.; et al.
Summary: Background: In the large randomised NEPTUNE study, peginterferon alfa‐2a 180 μg/wk for 48 weeks produced higher hepatitis B e antigen (HBeAg) seroconversion rates 24 weeks post‐treatment (36%) than a lower dose (90 μg/wk) and/or shorter duration (24 weeks) (range 14%‐26%). Aim: To determine seroconversion rates 5 years after completion of treatment in NEPTUNE. Methods: HBeAg‐positive patients who completed 24 weeks' follow‐up in NEPTUNE (with peginterferon alfa‐2a 90 μg/wk × 24 weeks [group 1]; 180 μg/wk × 24 weeks [2]; 90 μg/wk × 48 weeks [3] or 180 μg/wk × 48 weeks [4]) were followed up. Results: Three hundred and eighty three of the 544 patients in the original study were enrolled in the long‐term follow‐up study. Many patients (196 overall; more in groups 1‐3 than 4) received nucleos(t)ide analogues or immunomodulators during follow‐up, and more patients had missing data at year 5 in groups 2 and 4 (48 weeks, 50/112) than in groups 1 and 3 (24 weeks, 23/103), which confounds the planned per‐protocol analysis. HBeAg seroconversion rates in groups 1, 2, 3 and 4 at year 5 were 47.5%, 50.7%, 52.2% and 67.1%, respectively, (odds ratio for group 4 versus 1‐3: 2.02; 95% CI 1.21, 3.38), using multiple imputation methods for missing measurements. Conclusion: Seroconversion rates are durable for up to 5 years after completion of peginterferon alfa‐2a therapy and, consistent with NEPTUNE, the results suggest that the licensed regimen (180 μg × 48 weeks) is more efficacious for HBeAg‐positive patients than a lower dose and/or shorter treatment duration. Abstract : Linked Content This article is linked to Wei and Nguyen paper. To view this article visithttps://doi.org/10.1111/apt.14657 .